Metode Tabarak Dalam Meningkatkan Kemampuan Hafalan Al-Qur’an Siswa - Irfan Teo Fernando; Rini Rahman (KOLONI, 2024)
This research is motivated by the issue of children's low ability to memorize the Qur'an, which is lower compared to other prominent regions. Therefore, a Qur'an memorization method was developed to enhance students' memorization skills using the Tabarak method. The implementation of the Tabarak method at Rumah Tahfidz Ladunni utilizes audiovisual aids, with speakers and microphones to listen to the recitation of the verses to be memorized, which are repeated an average of twenty times. The purpose of this research is to understand the Tabarak method in improving students' memorization abilities. The method used in this research is a qualitative field research method. The techniques used for data collection are observation, interviews, and documentation. The results of the research indicate that the use of the Tabarak method at Rumah Tahfidz is effective, as students are able to memorize the Qur'an with proper articulation and Tajweed in a relatively short time within the region. The Tabarak method enables students to memorize well and enjoy the process of learning to memorize the Qur'an